Radial extracorporeal shock wave therapy improves pain and plantar pressure in patients with early-to-mid-stage unilateral knee osteoarthritis: a retrospective before-after controlled study - Yang, Tianxiang; Ma, Tao; Liu, Xueqi; Wang, Yi; Wang, Yinbin; Chen, Xi; Wei, Haicheng; Chen, DeSheng (Frontiers in Medicine, 2025)
ObjectiveTo investigate the effects of radial extracorporeal shockwave therapy (rESWT) on pain and plantar pressure in patients with early-to-mid-stage unilateral knee osteoarthritis (KOA).MethodsFifty patients with early-to-mid-stage KOA who received treatment at the Extracorporeal Shockwave Therapy Clinic of the People's Hospital of Ningxia Hui Autonomous Region between January 2025 and June 2025 were selected. General patient data, Visual Analog Scale (VAS) scores for pain, Lequesne index scores, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, and plantar pressure results before and after treatment were collected.ResultsVAS scores at all post-treatment assessment time points were significantly decreased compared to pre-treatment values (all P < 0.05). Post-treatment, the Heel Force Weight percentage (HFW) decreased, while the High-Pressure Point (HPP), Average Pressure (AP), Foot Body Weight percentage (FBW), Contact Area (CA), and Forefoot Force Weight percentage (FFW) increased compared to pre-treatment values (all P < 0.05). Dynamic plantar pressure in the third and fourth metatarsals (M34), fifth metatarsal (M5), arch (FM), and heel (FH) significantly increased after treatment (all P < 0.05). The Lysholm score increased and the WOMAC score decreased significantly after treatment (all P < 0.05).ConclusionrESWT can significantly alleviate knee joint pain and promote the recovery of knee joint function in patients with KOA, thereby reducing the degree of abnormality in plantar pressure distribution.